Econometric Model of Economic Growth in Indonesia Using the SYS and FD-GMM Approach - Alfiyana, Siti; Astuti, Hartiningsih; Susilo, Joko Hadi; Endang, Endang (Eko-Regional: Jurnal Pembangunan Ekonomi Wilayah, 2024)
This study aims to determine the model of Indonesia's economic growth in 2013-2022 with dynamic panel data through the SYS-GMM and FD-GMM approaches, so that the variables that influence short-term and long-term economic growth can be identified. The research method used is quantitative descriptive analysis. The data used comes from the Central Statistics Agency of 34 provinces in Indonesia 2013-2022. This study found that economic growth was significantly positively influenced by the variables of inflation, foreign investment, and household consumption. Economic growth is significantly negatively affected by domestic investment variables, regional minimum wages, and open unemployment rates. Inflation, foreign investment, and household consumption have short-term impacts on economic growth, while domestic investment, regional minimum wages, and the open unemployment rate have long-term impacts on economic growth. Research finds economic growth is influenced by the previous year. The policy implication is that the government focuses on factors that increase economic growth.